High performance vehicular connectivity using opportunistic erasure coding - Mahajan, Ratul; Padhye, Jitu; Agarwal, Sharad; Zill, Brian (USENIX Annual Technical Conference, 2012)
Motivated by poor network connectivity from moving vehicles, we develop a new loss recovery method called opportunistic erasure coding (OEC). Unlike existing erasure codingmethods, which are oblivious to the level of spare capacity along a path, OEC transmits coded packets only during instantaneous openings in a path’s spare capacity. This transmission strategy ensures that coded packets provide as much protection as the level of spare capacity allows, without delaying or stealing capacity fromdata packets. OEC uses a novel encoding that greedily maximizes the amount of new data recovered by the receiver with each coded packet. We design and implement a system called PluriBus that uses OEC in the vehicular context. We deploy it on two buses for two months and show that PluriBus reduces the mean flow completion time by a factor of 4 for a realistic workload. We also show that OEC outperforms existing loss recovery methods in a range of lossy environments.